Injuries among Amish children: opportunities for prevention - Stephen Strotmeyer; Abigail Koff; Joshua N. Honeyman; Barbara A. Gaines (BMC, 2019)
Abstract Objectives The purpose of this study was to examine the injury risk patterns among Amish children, many of whom may be exposed to uncommon injuries and limited access to care due to their agrarian lifestyle and remote communities. Design Retrospective Chart Review. Methods With IRB approval, we performed a retrospective review of Amish patients age ≤ 12 years presenting to a level I pediatric trauma center between January 1, 2005, and December 31, 2015. Data abstracted from the institutional trauma registry and electronic medical record were analyzed using descriptive statistics and univariate/multivariate analysis. Results One hundred eighty-three Amish children were admitted, and 2 died from injuries. Patients were 72.1% male; the median age was 5 (IQR 3-8); median injury severity score (ISS) was 9 (IQR 4-14), Most injuries were the result of blunt force trauma (91.8%). The most frequent mechanisms were falls (42.6%), followed by animal-related (15.3%), and buggy (12.5%). Most injuries occurred at home (44.4%) or on a farm (33.9%). Hay hole falls were a unique source of injury with a high ISS (12; IQR 6-17). The overall median length of stay (LOS) was 2 days (IQR 1-3), with animal-related injuries associated with the longest LOS (3 days; IQR 1-4.75). Conclusions The majority of injuries among Amish children are due to falls. Hay hole falls and animal-related injuries result in the highest ISS and longest LOS. These findings identify the farm as a potential target for culturally appropriate interventions for risk modification.